2023
DOI: 10.3390/jcs7040138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Eco-Friendly Hemp-Fiber-Reinforced Recycled HDPE Composites

Abstract: The exploitation of natural fibers to reinforce polymers is a promising practice. Thus, biocomposites have gained increased attention in automotive, construction, and agricultural sectors, among others. The present work reports the reinforcement of recycled high-density polyethylene (r-HDPE) with hemp fibers to afford composite materials as sustainable analogues to conventional wood/plastic composite (WPC) products. HDPE bottles (postconsumer waste) were used as r-HDPE and further reinforced by the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 64 publications
1
16
1
Order By: Relevance
“…Notably, composites reinforced with 30 wt % PFs exhibited a remarkable 160% increase in Young’s modulus compared to PA6 matrices. Unlike numerous studies in the existing literature, , , this exceptional tensile characteristic was achieved without resorting to expensive or laborious chemical modifications of PFs. The notable improvements were primarily observed in PA6-based composites, supporting the favorable compatibility of the pulp fibers with PA6 when prepared by using the premixing ball milling method.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Notably, composites reinforced with 30 wt % PFs exhibited a remarkable 160% increase in Young’s modulus compared to PA6 matrices. Unlike numerous studies in the existing literature, , , this exceptional tensile characteristic was achieved without resorting to expensive or laborious chemical modifications of PFs. The notable improvements were primarily observed in PA6-based composites, supporting the favorable compatibility of the pulp fibers with PA6 when prepared by using the premixing ball milling method.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, the weight loss in this phase corresponds to the different reinforcement loads of the fibers. Other authors have also reported these ternary degradation profiles for PA6-based composites loaded with other cellulose-based fibers. , When incorporating high quantities of PFs, the onset thermal degradation temperature drops shown in the specific 30 wt % case cause a temperature drop from 387 to 344 °C, due to the conversion of cellulose into acetaldehyde, propenal, methanol, and acetic acid . Espinach et al explored the thermal properties of polymer composites that were reinforced with bleached kraft softwood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing the studies in the systematic review found that different types of postconsumer plastics were used as waste in the evaluated experiments. Among the most prevalent typologies, polypropylene (PP) was highlighted in five studies [14][15][16]19,22], and high-density polyethylene (HDPE) in another five studies [16,[19][20][21][22]. Additionally, polyethylene terephthalate (PET) was used in a specific study [24].…”
Section: [23]mentioning
confidence: 99%
“…Additionally, plant-based fillers, such as crushed wood waste, pine nut shells, corn husks, hemp fibers, and wood chips, were incorporated to improve mechanical properties and reduce reliance on virgin materials. and high-density polyethylene (HDPE) in another five studies [16,[19][20][21][22]. Addi polyethylene terephthalate (PET) was used in a specific study [24].…”
Section: [23]mentioning
confidence: 99%